Modeling of drug delivery from erodible and non-erodible laminated planar devices into a finite external medium - Helbling, Ignacio Marcelo (2010)
Analytical solutions based on the pseudo-steady state approximation (PSSA) were derived for the case of controlled dispersed-drug release from erodible and non-erodible planar matrices, through a membrane, and taking into account the existence of a diffusion boundary layer and a finite release medium. The solutions can be applied to a broad range of situations from drug release into finite or infinite medium, from erodible or non-erodible matrices, in the presence or absence of a membrane, and in the presence or absence of a stagnant liquid layer. The prediction is accurate for the cases in which the initial drug load is higher than the drug solubility in the polymer (e.g. A/Cs mayor o igual a 3) till the entire dispersed drug is dissolved. The dependence on the release kinetics with different parameters was simulated and provides a theoretical platform for the design of dispersed drug release devices.